2015 5th International Youth Conference on Energy (IYCE) 2015
DOI: 10.1109/iyce.2015.7180746
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the image produced by Scheffler paraboloidal concentrator

Abstract: Our purpose is to help projects of receivers for Scheffler concentrators in order to avoid losses of energy at the entrance of thermal radiation absorbers. The Scheffler concentrator is a paraboloidal solar concentrator that works in a two axes track system and, thus, maintains the focal image fixed in its stopped absorber with the variation of the solar declination and azimuth. The image formed by Scheffler concentrator is presented. The reflector geometry is defined by a lateral section of a paraboloid and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Since the Sun makes a cone of angle 0.54 at every point on the reflector surface, the reflected rays from these points also form a cone resulting in an elliptical image at the focal plane. 30 The reflected light cone from the topmost point E1 envelops the images created by the light from all other points.…”
Section: Scheffler Reflectormentioning
confidence: 99%
“…Since the Sun makes a cone of angle 0.54 at every point on the reflector surface, the reflected rays from these points also form a cone resulting in an elliptical image at the focal plane. 30 The reflected light cone from the topmost point E1 envelops the images created by the light from all other points.…”
Section: Scheffler Reflectormentioning
confidence: 99%
“…38 Solar rays trace a cone with an angle 2θ s , with θ s ≈ 0.27 on the surface of the Earth. 39 The image on the focal plane perpendicular to the center line of the reflected ray will ideally assume an amplitude Δr given by Equation (12), where p is the distance from the generic point R x R ,y R ð Þon the surface of the concentrator to the focal point F as shown in Figure 2 40 :…”
Section: Scheffler Reflector Geometrymentioning
confidence: 99%
“…The effects of aperture area variations in the focal image size were studied mathematically by Dib and Fiorelli (2015), and by photogrammetry and Ray Tracing by Ruelas, Pando, Lucero, and Tzab (2014) Ruelas, Palomares, and Pando (2015). Considering a perfect concentrator and perfect tracking system, Dib and Fiorelli found that the variations in aperture area reach the limits of +37% and -38% between both solstices, and when the image is smaller, the aperture area is larger and the concentrated ratio is highest.…”
Section: Introductionmentioning
confidence: 99%